Ordinances of the Borough of Vineland 5 (1883) - (:unkn) unknown (My University, 1883)
An Ordinance for the Protection of Persons and Property, 3 of Ordinance No. 3: And be it ordained and enacted, That if any person shall unnecessarily fire or cause to be fired, any gun, pistol or other fire-arms or cannon, in any of the street, lanes, alleys or parks of said Borough [i.e., the Borough of Vineland]; or if any person under the age of fifteen years shall carry or use any gun, pistol or other fire-arms, or if any merchant or trader shall sell or offer to sell any gun, pistol or other fire-arms to any such person, he or they so offending shall be liable to a fine of not less than one nor more than ten dollars for every such offence."
Keywords: DISCHARGE; POSSESSION - MINORS; TRANSFER - MINORS